Correlation and Path Coefficient Analysis of Kopyor Dwarf Coconut (Cocos nucifera L.) - Miftahorrachman; Mawardi, Sukmawati; Novarianto, Hengky (International Coconut Community Journal, 2017)
Breeding programs of kopyor dwarf coconut require a population base with high genetic diversity especially for characters that relate to fruit production. The study aims to determine the appearance of three kopyor dwarf coconuts from Pati District and correlations among 13 characters of Kopyor Green Dwarf, Kopyor brown dwarf, and Kopyor Yellow Dwarf and to study twelve vegetative and generative characters which directly and indirectly affect the number of fruits. The study was conducted at The Paniki Experimental Garden, North Sulawesi, Indonesia from August 2015 to February 2016. The design used was randomized block design with three treatments and three replications. Observed thirteen characters including number of bunches (NB), number of fruit (NF), number of leaves (NL), number of leaflets (NLL), width of leaflets (WLL), length of the leafleats (LLL), length of petiole (LP), width of petiole (WP), thick of petiole (TP), length of rachis (LR), length of leaf (LL), height of stem (HS), and girth of stem (GS). Path analysis among morphological characters to number of fruits was worked out using the formula of Singh and Chaudary. Results of variance analysis showed Kopyor Green Dwarf and Kopyor Brown Dwarf significantly differed from Kopyor Yellow Dwarf. Results of simple correlation analysis found no correlation among twelve characters with number of fruits for the three kopyor dwarf coconut, but the results of the path analysis of characters NL (r=0.5627), NLL (r=0.5920), HS (r=0.4861), and GS (r=0.6123) for the Kopyor Green Dwarf; NB (r=0.4241), LP (r =0.6390) , WP (r = 0.8705), LR (r = 0.5235), and LL (r = 0.6257) for the Kopyor Brown Dwarf; and WLL (r = 0.8413), LLL (r = 0.5617), TP (r = 0.5864), LR (r =1.5795), and LL (r = 1.0228) for the Kopyor Yellow Dwarf directly affect the number of fruits. These characters can be used for basic selection in breeding of kopyor coconut.